PENDAMPINGAN PENYUSUNAN PERANGKAT PEMBELAJARAN DI SMK PLUS ALMUJAHIDI GUMUKMAS JEMBER - Yudianto, Erfan; Trapsilasiwi, Dinawati; Kurniati, Dian; Panglipur, Indah Rahayu (STKIP PGRI SITUBONDO, 2024)
Carrying out teaching and learning activities is not valid if it is not equipped with learning tools. This made the Minister of Education, Culture, Research and Technology, Mr. Nadim Makarim, simplify the existing learning tools with one sheet of lesson plans. However, even though the name is 1 sheet, many teachers still feel doubtful and uncertain about whether there is really only 1 sheet. This is a problem for teachers at SMK Plus Al Mujahidi Gumukmas Jember. The school principal, through the head of the curriculum, invited the team to this activity. The methods used lecture, question and answer, discussion and practice. The results obtained from this activity are the teachers' understanding of how the 1 sheet RPP, LKPD, assessment and scoring rubric work. The practice carried out in this activity refers to one-on-one mentoring between the teacher and the service team